Genome-wide profiling of microRNAs: from scientist benchside to patient bedside - Calin, George (Henry Stewart Talks, 2009)
Central dogma of molecular oncology, MicroRNA and messenger RNA, Small RNAs make a big splash, A model for HE-miRNA mediated control of human haematopoiesis, Alterations of microRNAs are found in every type of human tumors, MicroRNAs as oncogenes and tumor suppressors, miR-15 and miR-16 induce apoptosis by targeting BCL2, They target multiple apoptosis and cancer related genes, MicroRNA-29 family, MiRNA profiling as a new diagnostic and prognostic tool for cancer patients, A unique miRNA signature is associated with CLL progression, Cancer predisposition: from epidemiology to genetics, About humans and mice: same gene, same mutation, same disease, Mutations in microRNA primary transcripts, The "field effect" of miRNA expression, The missing link in cancer predisposition, MicroRNAs as new therapeutic targets and new drugs, Principles of miRNA-based gene therapy and in vivo inhibition of miRNA in cancer cells, Ultraconserved non-coding genes: the new chapter of the textbook, A never ending revolution: other ncRNAs could be associated with cancer, UCG expression profiles classify human cancers, miRNA-ncRNA interactions, Non-coding RNAs as oncogenes
Archived at 2021/02/25